Hyperactivation of p53 contributes to mitotic catastrophe in podocytes through regulation of the Wee1/CDK1/cyclin B1 axis - Jie Feng; Liyi Xie; Wanhong Lu; Xiaoyang Yu; Hongjuan Dong; Yuefeng Ma; Ranran Kong (Renal Failure)
Podocyte loss in glomeruli is a fundamental event in the pathogenesis of chronic kidney diseases. Currently, mitotic catastrophe (MC) has emerged as the main cause of podocyte loss. However, the regulation of MC in podocytes has yet to be elucidated. The current work aimed to study the role and mechanism of p53 in regulating the MC of podocytes using adriamycin (ADR)-induced nephropathy. In vitro podocyte stimulation with ADR triggered the occurrence of MC, which was accompanied by hyperactivation of p53 and cyclin-dependent kinase (CDK1)/cyclin B1. The inhibition of p53 reversed ADR-evoked MC in podocytes and protected against podocyte injury and loss. Further investigation showed that p53 mediated the activation of CDK1/cyclin B1 by regulating the expression of Wee1. Restraining Wee1 abolished the regulatory effect of p53 inhibition on CDK1/cyclin B1 and rebooted MC in ADR-stimulated podocytes via p53 inhibition. In a mouse model of ADR nephropathy, the inhibition of p53 ameliorated proteinuria and podocyte injury. Moreover, the inhibition of p53 blocked the progression of MC in podocytes in ADR nephropathy mice through the regulation of the Wee1/CDK1/cyclin B1 axis. Our findings confirm that p53 contributes to MC in podocytes through regulation of the Wee1/CDK1/Cyclin B1 axis, which may represent a novel mechanism underlying podocyte injury and loss during the progression of chronic kidney disorder.